Change in the rate of pseudo[1]rotaxane formation by elongating the alkyl-chain-substituted diphenylethynylene linked to permethyl α-cyclodextrin. Issue 27 (2nd July 2020) - Ishino, Saqura; Masai, Hiroshi; Shimada, Sotaro; Terao, Jun
Graphical abstract: Highlights: The k of pseudo[1]rotaxane formation showed different trends over three regions of flexible chain length. The alkyl chains behaved as dampers or accelerators depending on their length. The kinetics of pseudo[1]rotaxane formation are dictated by structure. The findings guide the process of forming new host–guest complexes. Abstract: Herein, we report the kinetics of pseudo[1]rotaxane formation from permethyl α-cyclodextrin attached to a flexible-chain-substituted diphenylethynylene. When the chain is an alkyl group, the rate of formation shows different trends over three regions of chain length: deceleration (chain length = 1–3), acceleration (4–8), and re-deceleration (>12). This behavior is driven by a relative decrease in the Δ H ‡ of the transition.